Twelve-Month Outcomes of Combined Phacoemulsification with Ab Interno Canaloplasty Versus Single-Use Dual Blade Goniotomy in Glaucoma Patients - Prinz, Julia; Plange, Niklas; Schellhase, Hannah; Walter, Peter; Fuest, Matthias; Koutsonas, Antonis; Kuerten, David (Klinische Monatsblätter für Augenheilkunde, 2025)
Background To compare the efficacy and safety of combined phacoemulsification with ab interno canaloplasty (Phaco-AbiC) versus single-use dual blade goniotomy (Phaco-DBG).Material and Methods In this prospective consecutive case series, intraocular pressure (IOP), the number of IOP-lowering medications, the mean deviation (MD) of visual field testing, and surgery-related complications were evaluated in 25 eyes following Phaco-AbiC and 20 eyes following Phaco-DBG through 12 months of follow-up. Qualified or complete success was defined as postoperative IOP lower than 21, 18, and 16 mmHg with or without IOP-lowering medications.Results At the 12-month follow-up, IOP was significantly reduced compared to baseline in the Phaco-AbiC (14.2 ± 2.7 versus 19.2 ± 4.7 mmHg, p < 0.001) and Phaco-DBG groups (16.7 ± 3.4 versus 19.9 ± 3.9 mmHg, p < 0.001). At the 12-month follow-up, IOP was significantly higher following Phaco-DBG than Phaco-AbiC (p = 0.011). Compared to baseline, the number of IOP-lowering medications was significantly reduced in the Phaco-AbiC (1.2 ± 1.4 versus 2.4 ± 1.0, p < 0.001) and Phaco-DBG groups (0.8 ± 0.9 versus 2.1 ± 0.9, p < 0.001) at the 12-month follow-up. For IOP lower than 16 mmHg, the complete and qualified success rate was significantly higher following Phaco-AbiC (36.0 and 76.2%, respectively) than Phaco-DBG (17.5 and 40.6%; p = 0.037; p = 0.007, respectively). No severe intra- or postoperative complications occurred.Conclusion Both Phaco-AbiC and Phaco-DBG achieved a significant reduction in IOP and IOP-lowering medications at the 12-month follow-up. IOP was significantly lower 12 months following Phaco-AbiC than Phaco-DBG.
Keywords: glaucoma; canaloplasty; goniotomy; MIGS; phacoemulsification